Penyusunan Tes Psikologi Form A Online untuk Surat Izin Mengemudi (SIM) - Septiarly, Yashinta Levy; Widarnandana, I Gde Dhika; Ariani, Nyoman Wiraadi Tria; Putra, I Dewa Gede Udayana; Maharani, Komang Sinta; Putra, I Putu Brian Obie (Jurnal Psikologi Udayana, 2022)
Driving behavior is one of the routine activities carried out by individuals on a daily basis, both with two wheeled and four wheeled vehicles. A driver who drives his vehicle can see driving activity is a complex activity. So to be able to drive safely, responsibly and have good driving ethics and behavior, one must also have certain psychological aspects to support soft skills consisting of cognitive, affective and personality. Based on this, the researcher tried to arrange a Form A Psychological Test to obtain a Driver’s License. Psychological Test Form A is administered both online and offline. The construction of the test was carried out based on three aspects of the National Police Chief Regulation No. 5 Year 2021. The items of the psychological test form A have gone through field testing with 41 participants who already have a driving license (SIM) and were selected based on the results of the content validity evaluation with expert judgment, the level of diffilcuty and discriminatory power of the item, and the reliability of each sub aspect. Psychological test form A consist of three aspect and nine sub aspects with a total of 57 items, which has a reliability coefficient of each moving between 0.639 to 0.936.